2008
DOI: 10.1088/0953-8984/20/36/365211
|View full text |Cite
|
Sign up to set email alerts
|

Non-affine deformation in microstructure selection in solids II: Elastoplastic theory for the dynamics of solid state transformations

Abstract: We study the nucleation dynamics of a model solid state transformation and the criterion for microstructure selection. Using a molecular dynamics (MD) simulation, we had shown that the dynamics of the solid is accompanied by the creation of transient non-affine zones (NAZ), which evolve with the rapidly moving transformation front. Guided by our MD results, we formulate a dynamical continuum theory of solid state transformation, which couples the elastic strain to the non-affine deformation. We demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…We showed that the coupled dynamics of density fluctuations and elastic strain determined the microstructure of the growing nucleus. In this, and in a companion paper [8] we provide a more refined understanding of solid state nucleation and microstructure selection. Part I of a set of two papers deals with the results of our extensive MD simulations: we show that internal stresses generated during the transformation create local non-affine zones (NAZ) beyond a threshold stress.…”
Section: Introductionmentioning
confidence: 96%
“…We showed that the coupled dynamics of density fluctuations and elastic strain determined the microstructure of the growing nucleus. In this, and in a companion paper [8] we provide a more refined understanding of solid state nucleation and microstructure selection. Part I of a set of two papers deals with the results of our extensive MD simulations: we show that internal stresses generated during the transformation create local non-affine zones (NAZ) beyond a threshold stress.…”
Section: Introductionmentioning
confidence: 96%
“…In this paper, we lend further support to this claim by investigating this problem from the point of view of a phenomenological elasto-plastic theory [7] of the square to oblique transformation. The elasto-plastic theory has been shown earlier to reproduce the qualitative features of the results of our MD simulations [5].…”
Section: Introductionmentioning
confidence: 59%
“…Our theory allows us to determine the microstructure and the overall shape of a solid undergoing a square to a general oblique lattice. Unlike previous work in this subject [9] we allow for the presence of non-affine, or plas-tic deformations [5,7].…”
Section: Elasto-plastic Theorymentioning
confidence: 99%
“…Recent advances in confocal imaging methods have resulted in a flurry of experimental work studying phase transformation kinetics of colloidal solids via confocal laser scanning microscopy(CLSM) [1,[33][34][35]. While there has been much theoretical work dedicated to studying solidsolid phase transformations [7][8][9][10][11][12][13][14]36], there has been no coherent comparison of the colloids experiments with theory.…”
Section: Introductionmentioning
confidence: 99%